The Value of a Life: New Evidence from the Marketplace - Dardis, Rachel (American Economic Review, 1980)
Problems of life valuation have been discussed extensively in recent years (see Jan Acton; Brian C. Conley; Jack Hirshleifer, Theodore Bergstrom, and Edward Rappaport; M. W. Jones-Lee, J. Linnerooth, E. J. Mishan, Thomas Schelling, Richard Thaler and Sherwin Rosen, Dan Usher, and Richard Zeckhauser). Various approaches have been discussed, including the individual's willingness to pay for a risk reduction. This approach is favored by many economists on the grounds that it incorporates the preferences of the individual towards risk. Procedures for estimating the value of risk reduction to the individual include: 1) questionnaires; 2) risk premiums for workers in hazardous occupations; and 3) voluntary purchases of safety devices or products with safety features. While the questionnaire method and the risk premium method have been employed by several researchers, lack of market data has precluded the use of the third method. This paper investigates voluntary purchases of smoke detectors to estimate consumer willingness to pay for risk reduction. Such data may in turn be used to estimate the implicit value of a life.